Adaptation of a Commercial Qualitative BAX® Real-Time PCR Assay to Quantify Campylobacter spp. in Whole Bird Carcass Rinses - Bodie, Aaron R.; Dittoe, Dana K.; Applegate, Savannah F.; Stephens, Tyler P.; Ricke, Steven C. (Foods, 2023)
Poultry is the primary reservoir of Campylobacter, a leading cause of gastroenteritis in the United States. Currently, the selective plating methodology using selective agars, Campy Cefex and Modified Charcoal Cefoperazone Deoxycholate agar, is preferentially used for the quantification of Campylobacter spp. among poultry products. Due to the specific nature of Campylobacter, this methodology is not sensitive, which can lead to skewed detection and quantification results. Therefore, Campylobacter detection and quantification methods are urgently needed. The objective was to develop a shortened enrichment-based quantification method for Campylobacter (CampyQuant™) in post-chill poultry rinsates using the BAX® System Real-Time PCR assay for Campylobacter. The specificity and sensitivity for the detection of C. jejuni, C. coli, and C. lari in pure culture were determined. The BAX® System Real-Time PCR assay consistently detected and identified each species 100% of the time with an enumeration range of 4.00 to 9.00 Log10 CFU/mL. Enrichment time parameters for low-level concentrations (0.00, 1.00, and 2.00 Log10 CFU/mL) of Campylobacter using the BAX® System Real-Time PCR assay were elucidated. It was determined that an enrichment time of 20 h was needed to detect at least 1.00 Log10 CFU/mL of Campylobacter spp. Using the BAX® System Real-Time PCR assay for Campylobacter. As a result, time of detection, detection limits, and enrichment parameters were used to develop the CampyQuant™ linear standard curve using the detected samples from the BAX® System Real-Time PCR assay to quantify the levels in post-chill poultry rinsates. A linear fit equation was generated for each Campylobacter species using the cycle threshold from the BAX® System Real-Time PCR assay to estimate a pre-enrichment of 1.00 to 4.00 Log10 CFU/mL of rinsates detected. The statistical analyses of each equation yielded an R2 of 0.93, 0.76, and 0.94 with a Log10 RMSE of 0.64, 1.09, and 0.81 from C. jejuni, C. coli, and C. lari, respectively. The study suggests that the BAX® System Real-Time PCR assay for Campylobacter is a more rapid, accurate, and efficient alternative method for Campylobacter enumeration.